Influence of a Multimodal and Multimodal-Aerobic Therapy Concept on Health-Related Quality of Life in Breast Cancer Survivors. (February 2019) - Poier, Désirée; Büssing, Arndt; Rodrigues Recchia, Daniela; Beerenbrock, Yvonne; Reif, Marcus; Nikolaou, Andreas; Zerm, Roland; Gutenbrunner, Christoph; Kröz, Matthias
Context: Cancer-related fatigue (CRF) is one of the most burdensome symptoms in breast cancer survivors (BCSs), accompanied by reduced health-related quality of life (HRQOL).Objectives: This study investigated the influence of a multimodal therapy (MT; psychoeducation, eurythmy therapy, painting therapy, and sleep education/restriction), or a combination therapy (CT; MT plus aerobic training [AT]) on HRQOL in BCS with chronic CRF in comparison with AT alone.Methods: One hundred and twenty-six BCSs with CRF were included in a pragmatic comprehensive cohort study and allocated either per randomization or by preference to MT, CT, or AT. The EORTC QLQ-C30 core questionnaire was used to measure HRQOL. All analyses on HRQOL parameters were done in an explorative intention.Results: Patients were assigned to MT (n = 44), CT (n = 54), or AT (n = 28). CT was significantly superior to AT after 10 weeks of intervention (T1) in improving physical function. MT was found to have significant superiority over AT at T1 and T2 for physical functioning, emotional functioning, insomnia, and financial problems as well as role functioning, cognitive, social functioning, and fatigue 6 months later (T2).Conclusion : A multimodal approach appears to be a suitable concept for BCS with chronic CRF. A confirmatory study with larger samples should demonstrate the superiority of MT and adapted CT in HRQOL compared with the current treatment AT found in these explorative analyses.